2009
DOI: 10.1139/t08-127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies of the hydromechanical behaviour of a natural unsaturated swelling soil

Abstract: This paper presents experimental studies performed on a natural swelling soil. Initially, the soil fabric was studied by a mercury porosimetry test, revealing a clear bimodal pore distribution that corresponds to micro- and macrostructural levels. The water-retention curve of the soil was then determined using two suction-imposition techniques: the osmotic and the vapour equilibrium methods. During the main testing program, three successive wetting and drying cycles were applied in a suction range between 0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The volume change potential (VCP) under cyclic W/D shows different behavior responses. Some studies, e.g., [5,6,9,44,45,48], have concluded that this cyclic process results in cumulative swell strains, while others have shown swell fatigue (i.e., accumulated shrinkage), e.g., [1,3,4,8,13,24,32,[36][37][38]47,49,50], and was explained as the soil particles exhibited continuous rearrangement, leading to a less active microstructure. The results of [12][13][14]34,44] reported both swell and shrinkage accumulation at the end of this cyclic process.…”
Section: Introductionmentioning
confidence: 99%
“…The volume change potential (VCP) under cyclic W/D shows different behavior responses. Some studies, e.g., [5,6,9,44,45,48], have concluded that this cyclic process results in cumulative swell strains, while others have shown swell fatigue (i.e., accumulated shrinkage), e.g., [1,3,4,8,13,24,32,[36][37][38]47,49,50], and was explained as the soil particles exhibited continuous rearrangement, leading to a less active microstructure. The results of [12][13][14]34,44] reported both swell and shrinkage accumulation at the end of this cyclic process.…”
Section: Introductionmentioning
confidence: 99%
“…This includes exposure to wetting from the saturated host rock and drying from the hot nuclear spent fuel [48], which makes the characterisation of the water retention behaviour of these materials particularly important. The water retention behaviour of clays is also relevant to other applications including, for example, the prediction of settlements under superficial foundations, the study of groundwater flow and the design of agricultural irrigation systems [3,44,69].…”
Section: Introductionmentioning
confidence: 99%
“…This behavior was explained by the continuous rearrangement of the soil particles, leading to a less active microstructure. In contrast, Chu and Mou [5], Pousada [6], Nowamooz [7] and Nowamooz et al [8] observed the opposite effect, in which the amount of swelling strains increases with the number of successive cycles. All of these tests showed that the equilibrium elastic state could be reached at the end of several cycles.…”
Section: Introductionmentioning
confidence: 99%